2013
DOI: 10.1097/jom.0b013e3182a2a5e1
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Mental and Physical Health and Coping Style on Work Ability

Abstract: Successful coping styles and good health predict high work ability, and thus, promoting such factors can help improve sustainable employability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
31
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 34 publications
2
31
1
Order By: Relevance
“…Stressrelated eating and drinking is one pattern of passive coping to relieve stress. Associations between stress-related eating and drinking and work ability have not been studied earlier, but avoidant coping has been associated with decreased work ability [21].…”
Section: Introductionmentioning
confidence: 99%
“…Stressrelated eating and drinking is one pattern of passive coping to relieve stress. Associations between stress-related eating and drinking and work ability have not been studied earlier, but avoidant coping has been associated with decreased work ability [21].…”
Section: Introductionmentioning
confidence: 99%
“…Work ability can be divided into two aspects: mental and physical. Although it is known that mental and physical health has a different impact on self-reported work ability (van de Vijfeijke et al 2013), it is still unclear how the self-reported mental and physical work ability relates to the appraisal of overall work ability. According to a study of Klasan et al (2013), the aspect that predicts low work ability in ambulance workers best is the amount of strenuous physical activity during work.…”
Section: Introductionmentioning
confidence: 99%
“…In an aging workforce, health problems will become more prevalent. Employees with health problems could be faced with decreased work ability (2), quantitative productivity loss at work (3,4), sickness absence (5), and even exit the labor force (6). Work ability can be defined as the balance between an individual's resources (eg, health, functional abilities, competencies) and work demands (eg, work environment, contents, demands) (7).…”
mentioning
confidence: 99%
“…Most findings on relations of health with work outcomes come from studies with a cross-sectional design. A few longitudinal studies have, however, shown that psychological health problems are related to an increased risk of sickness absence in the following year (5) and that especially general physical health is related to reduced work ability at one-year follow-up (2). These studies have used different definitions of health problems and work outcomes, which makes the comparison of the influence of different chronic health problems on work outcomes difficult.…”
mentioning
confidence: 99%